2021
DOI: 10.3390/pr9050785
|View full text |Cite
|
Sign up to set email alerts
|

Continuum-Based Approach to Model Particulate Soil–Water Interaction: Model Validation and Insight into Internal Erosion

Abstract: Resolving the interaction between soil and water is critical to understanding a wide range of geotechnical applications. In cases when hydrodynamic forces are dominant and soil fluidization is expected, it is necessary to account for the microscale interactions between soil and water. Some of the existing models such as coupled Computational Fluid Dynamics–Discrete Element Method (CFD-DEM) can capture microscale interactions quite accurately. However, it is often computationally expensive and cannot be easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The conclusion has reference value for how to estimate soil liquefaction. Ahmed Ibrahim [19] studied a continuum-based approach to model particulate soil-water interactions and gave a model of the internal fluidization of a sand bed due to an upward water jet. Zhang et al [20] studied the effect of soil liquefaction on the bearing capacity of suction anchors and found that when the soil liquefied, the suction anchors would fail completely.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion has reference value for how to estimate soil liquefaction. Ahmed Ibrahim [19] studied a continuum-based approach to model particulate soil-water interactions and gave a model of the internal fluidization of a sand bed due to an upward water jet. Zhang et al [20] studied the effect of soil liquefaction on the bearing capacity of suction anchors and found that when the soil liquefied, the suction anchors would fail completely.…”
Section: Introductionmentioning
confidence: 99%